2016
DOI: 10.1055/s-0035-1561662
|View full text |Cite
|
Sign up to set email alerts
|

Variations on the Blaise Reaction: Synthesis of 3,5-Dioxopentanoates and 3-Amino-5-oxopent-3-enoates

Abstract: in R O O R O NH 2 R O CN O OEt O Zn, THF reflux (ii) 3 N HCl (ii) aq K 2 CO 3 (50% w/v) (i) BrCH 2 CO 2 Et R: aryl, heteroaryl, t-Bu 13 examples; 55-81% R: aryl, heteroaryl, t-Bu 6 examples; 62-82% exclusive formation of the Blaise reaction products OEtAbstract We have achieved a facile and convenient synthesis of a variety of 3,5-dioxopentanoates (3,5-diketo esters) and 3-amino-5-oxopent-3-enoates by a zinc-mediated condensation of readily available 3-oxopropanenitriles (α-cyano ketones) with ethyl bromoaceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…20 In continuation of that work, we found that when acyl nitriles 10 are employed instead of alkyl or aryl nitriles, the reaction provides 3,5-diketo esters 11 (Scheme 2; Equation 3). 21 In the present work, we have further expanded the scope of the Blaise reaction by employing ethyl 4-bromocrotonate (12) instead of ethyl bromoacetate in the reaction with alkyl or aryl nitriles 5 to give pyridin-2-ones 13. We refer to this variation as the vinylogous Blaise reaction.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…20 In continuation of that work, we found that when acyl nitriles 10 are employed instead of alkyl or aryl nitriles, the reaction provides 3,5-diketo esters 11 (Scheme 2; Equation 3). 21 In the present work, we have further expanded the scope of the Blaise reaction by employing ethyl 4-bromocrotonate (12) instead of ethyl bromoacetate in the reaction with alkyl or aryl nitriles 5 to give pyridin-2-ones 13. We refer to this variation as the vinylogous Blaise reaction.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…2-Hydrazinylpyridine was prepared from 2-bromopyridine using a modified literature procedure (Klingele et al, 2010), as we have previously reported (Hiscock et al, 2019). �-Chloroacetylferrocene (Yang et al, 2007) and 3-oxo-3-(ferrocenyl)propanenitrile (Rao & Muthanna, 2016) were also prepared via modified literature procedures. All other reagents and starting materials were purchased from Sigma-Aldrich and used as purchased.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…: 174.2 °C, IR (KBr, νmax, cm -1 ): 3328, 3204, 3015, 2982, 1762, 1632, 1611, 1580, 1485, 1334, 1148, 1012, 961, 768; RESULTS AND DISCUSSION Starting material phenylthio β-keto ester (4) synthesized by employing Blaise reaction (Scheme-III). According to the Blaise reaction protocol acrylonitrile (1), thiophenol (2), ethylbromo acetate (3) treated with zinc and TMSCl provided phenylthio β-keto ester [26,27].…”
Section: General Procedures For Synthesis Of (4r5r)-ethyl 4phenyl-3-(mentioning
confidence: 99%